The prevalence of apical periodontitis in patients prior to hematopoietic cell transplantation: a systematic review - Letícia Tainá de Oliveira Lemes; Carolina Horn Troian-Michel; Theodoro Weissheimer; Marcus Vinicius Reis Só (Restorative Dentistry & Endodontics, 2024)
ObjectivesThis systematic review addressed the question: “What is the prevalence of apical periodontitis in patients prior to hematopoietic cell transplantation?”Materials and MethodsA systematic search was conducted in MEDLINE/PubMed, Cochrane Library, Scopus, Web of Science, Embase, and Grey Literature Report. Eligibility criteria were based on the condition, content, and population strategy: the condition was the radiographic prevalence of apical periodontitis, the content comprised patients scheduled for hematopoietic stem cell transplantation, and the population consisted of adult and pediatric patients. The revised Risk of Bias in Nonrandomized Studies of Exposure tool was used to assess the quality of studies. The Grading Recommendations Assessments, Development, and Evaluation (GRADE) tool was used to assess the quality of evidence.ResultsEight studies were included in this review. The average number of patients with apical periodontitis was 15.65% (range, 2.1%–43.34%). One study was classified as having a very high risk of bias, 1 with a high risk of bias, and 6 with some concern for bias. GRADE analysis showed a very low certainty of evidence. Significant limitations concerning the absence of control over confounding variables were identified.ConclusionsWith the caveat of the very low quality of evidence in the studies reviewed, there was a low to moderate prevalence of apical periodontitis in patients prior to undergoing hematopoietic cell transplantation.